STRATEGI SUPPLY CHAIN USAHA KECIL DAN MENENGAH DENGAN PENDEKATAN ANALISIS SWOT GUNA MENENTUKAN STRATEGI PENGEMBANGAN USAHA DAN PERSAINGAN PASAR - -, Sidarto (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2013)
In the firms, own small, medium or large in its development have been facing the environment, both the company's own internal environment and external environment of the company. Environmental changes force firms to adjust for the survival of the company itself. So is the Nudi Mulyo Farmers Cooperative, which up to now difficult to develop because of competition from businesses that are located not far from cooperative.One way to determine strategies for developing and managing the market competition is to formulate a strategy to compete with a SWOT analysis approach. In this analysis can be carried out by looking at the internal factors (strengths and weaknesses) that exist within the cooperative and also look at external factors (opportunities and threats). From the results of analysis using the SWOT matrix of the proposed strategy, the first by looking at the strengths and opportunities (SO) should be able to maintain the stability of the cooperative effort considering the number of people around the cooperative livelihood as farmers and farm laborers, while the cooperative it self already has a permanent legal entity, both by looking at the weaknesses and opportunities (WO) cooperative venture must have the courage to raise capital by way of cooperation with investors from the outside, the third with a look of strength and threat (ST) cooperative must be improved its service to customers to cope with competition getting tougher, fourth with a look at the weaknesses and threats (WT) to provide guidance to managers on how to define entrepreneurship and revisit flagship produc and pricing In the foreseeable future, a cooperative must have a clear vision and mission so easy to determine what strategy to do so the cooperative can progress and develop and be able to cope with market competition.